Assessment of the attitude, knowledge and practices of medical professionals about adverse drug reactions and their reporting during practice in government hospital and private setup - SUMAN A; QADRIE ZL; J. SRIKANTH (International Journal of Pharma and Bio Sciences, 2018)
The first remarkable Adverse drug reaction (ADR) reported in Japan was an anaphylactic shock due to penicillin although intradermal testing for antibiotics has been exercied as prediction method of anaphylactic shock for a long time, it was discontinued in 2004 because no evidence of prediction. The malformation of limbs(Phocomelia,1957) caused by thalidomide as global problem and drug was withdrawn from market in 1963. The study was conducted on health care professionals to assess the aptitude, knowledge and practice of adverse drug reactions reporting during their clinical practice. The importance of study is to identify whether the health care professionals in Suryapet are compliant towards the monitoring, prevention, treatment and reporting of Adverse drug reactions during their practice. From the study of two hundred questionnaires are distributed to health care professionals in which 190 of them replied and the response curve was found to be 95% out of hundred. Adverse Drug Reactions (ADRs); the response of the drug which is noxious and unintended, occurs at normal dose for using prophylaxis, diagnosis, or therapy of disease, or for the modifications of physiological function. The ADRs play a major role since 19th century which can lead to health complications from moderate to severe conditions from moderate to severe conditions of health complications, life threatening conditions and sometimes which can lead to death of the patient. The ADRs are measured by WHO scale. There are many ADRs that arise during the treatment arise while treating the patient or during the treatment. To monitor and prevent the ADRs in treatment, it is one of the most important factor to give better quality of life and compliance to patient through better quality of treatment. for better quality of treatment to give quality of life to the patient and better patient compliance. The statistical data collected by the study conducted on adverse drug reactions are evolved during treatment. It is based on the knowledge about ADRs and their reporting during practice of all health care professionals (Physicians, Clinical Pharmacists, Pharmacists, Nurses) working in government and private hospitals and clinics in Suryapet (Dist.) Telangana.